Mark McKerracher & Helena Hamerow (eds), New Perspectives on the Medieval ‘Agricultural Revolution’: Crop, Stock and Furrow - Morton, Benjamin (Medieval Settlement Research, 2024)
Book review of New Perspectives on the Medieval ‘Agricultural Revolution’: Crop, Stock and Furrow.